2023
DOI: 10.1111/jgh.16093
|View full text |Cite
|
Sign up to set email alerts
|

A novel smartphone scleral‐image based tool for assessing jaundice in decompensated cirrhosis patients

Abstract: Background and Aim: Serum bilirubin is an established marker of liver disease. Reliable tools for non-invasive assessment of jaundice in cirrhosis patients, at risk of clinical decompensation, are highly desirable. While smartphone-based imaging has been described in neonatal jaundice, it has not been investigated in advanced cirrhosis patients. Methods: We included 46 hospitalized patients with acute cirrhosis decompensation and jaundice. Scleral images using an Android smartphone were taken to derive "Sclera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…For assessing bilirubin levels in patients with cirrhosis, owing to the simpler image capture for the sclera, we recommend the use of the sclera as the imaging site. See our clinical paper presenting results based on the scleral imaging site and how they correlate with clinical scores such as Clinical Liver Failure Consortium Acute-Decompensation score and grade of Acute-on-Chronic Liver Failure [ 16 ]. The very strong correlation of predicted bilirubin via the sclera with TSB even at values greater than 20x the upper limit of normal, indicates promising clinical utility for real-world application.…”
Section: Discussionmentioning
confidence: 99%
“…For assessing bilirubin levels in patients with cirrhosis, owing to the simpler image capture for the sclera, we recommend the use of the sclera as the imaging site. See our clinical paper presenting results based on the scleral imaging site and how they correlate with clinical scores such as Clinical Liver Failure Consortium Acute-Decompensation score and grade of Acute-on-Chronic Liver Failure [ 16 ]. The very strong correlation of predicted bilirubin via the sclera with TSB even at values greater than 20x the upper limit of normal, indicates promising clinical utility for real-world application.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inclusion of serum bilirubin in clinical scoring systems for acute hepatic deterioration, scleral images taken from smartphones may serve as useful biomarkers for clinical parameters of disease severity. [12] Commercially available fitness and sleep trackers have also been studied in patients with cirrhosis to assess for covert HE. Buckholz et al collected sleep data from 25 patients using a multi-sensor device validated for 4-stage sleep detection.…”
Section: Smartphone Applicationsmentioning
confidence: 99%
“…In a study of 46 patients with alcohol-associated hepatitis, scleral images showed a strong correlation with serum bilirubin at baseline and over time. Given the inclusion of serum bilirubin in clinical scoring systems for acute hepatic deterioration, scleral images taken from smartphones may serve as useful biomarkers for clinical parameters of disease severity 12 …”
Section: Biometric Datamentioning
confidence: 99%